A REVIEW ON LIQUID CRYSTALLINE NANOPARTICLES (CUBOSOMES): EMERGING NANOPARTICULATE DRUG CARRIER - NAVEENTAJ, S.; MUZIB, Y. INDIRA (International Journal of Current Pharmaceutical Research, 2020)
Cubosomes are novel biocompatible drug delivery system and have honeycombed (cavernous) structures whose diameter size range from 10–500 nm. They appear like dots, which are likely to be spherical structures. Each dot corresponds to the presence of a pore containing aqueous cubic phase in the lipid water system. Cubosomes posse’s great significance in the field of cosmeceuticals and Pharmaceuticals due to its unique features and become an attractive choice of vehicle for in vivo drug delivery due to their low cost, safety, efficacy and versatility for controlled release application and functionalization. Cubosomes have a very simple method of preparation; biodegradability of selected lipids has the capability to encapsulate hydrophobic and hydrophilic substances. Cubosomes are considered to be versatile systems, and prepared cubosomes can be administrated by different ways such as oral, percutaneous and parenteral routes. On the whole, cubosomes offer high consequence in nano-based drug preparations for melanoma (skin cancer) treatment, targeted drug delivery systems and comprise a wide range of applications in many areas and are characterized by various parameters. Consequently, cubosomes are in progress forward of awareness in the Pharmaceutical division. This review article mainly focuses on the methods of preparation, advantages, and applications of cubosomes.